Students’ Test Anxiety in Science at Secondary Level in Private Schools for Boys and Girls in Danyore, District Gilgit - Ahmad, Shahzad; Jamil, Sadia; Fatima, Saba (JCTE, 2026)
Anxiety is a common human experience, although its intensity varies between individuals. It is generally described as an emotional state involving the anticipation of potential difficulties or unpleasant situations in the future. As a psychological condition, anxiety can manifest itself through physical, emotional, and social symptoms. A certain level of anxiety often influences how tasks are performed. In the academic context, students' performance in different subjects can be influenced by their level of test anxiety, making it essential to examine this factor. The present study aimed to explore the level of test anxiety among secondary school science students in Danyore area of Gilgit. The target population included the 921 tenth-grade science learners enrolled in local institutions, while the sample included 269 students from six private schools, chosen through convenience sampling due to time constraints. To measure test anxiety, the researcher applied the Test Anxiety Inventory (TAI), created by Spielberger (1980) and later used by Stefan Peter and Philip Zabek in similar contexts. Students’ anxiety levels were assessed using mean scores of individual items. Inferential statistics like t-test was used to compare the mean science test anxiety on gender basis. Effect size using Cohen’s d to determine the practical significance of differences was used. Results indicated that most students expressed a neutral stance regarding science test anxiety, with only a small proportion demonstrating a negative orientation. Interestingly, none of the participants reported positive perceptions of test anxiety. The gender analysis further showed that male and female students had similar levels of test anxiety.